2010
DOI: 10.1091/mbc.e09-07-0609
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 Regulates Macrophage Chemotaxis

Abstract: Using a targeted genetic deletion, we show that the S100A4 metastasis factor is required for macrophage recruitment to sites of inflammation in vivo. S100A4−/− primary macrophages display defects in chemotaxis due to myosin-IIA overassembly and altered CSF-1 receptor signaling. These studies establish S100A4 as a regulator of macrophage motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 92 publications
7
122
4
Order By: Relevance
“…In both models, no effect of S100A4 knockout was observed on reactive astrogliosis (GFAP staining), axonal or oligodendrocyte pathology (NF-200 or tau-1), or neuronal plasticity (GAP-43). Similarly, even though S100A4 has previously been shown to regulate macrophage chemotaxis 32 and thus it might affect post-traumatic inflammation, we did not find difference in the number of microglia/microphages in the sublesion zone (lectin staining). …”
Section: S100a4 Is Upregulated In Brain Injury and Protects Neuronscontrasting
confidence: 65%
“…In both models, no effect of S100A4 knockout was observed on reactive astrogliosis (GFAP staining), axonal or oligodendrocyte pathology (NF-200 or tau-1), or neuronal plasticity (GAP-43). Similarly, even though S100A4 has previously been shown to regulate macrophage chemotaxis 32 and thus it might affect post-traumatic inflammation, we did not find difference in the number of microglia/microphages in the sublesion zone (lectin staining). …”
Section: S100a4 Is Upregulated In Brain Injury and Protects Neuronscontrasting
confidence: 65%
“…Inflammatory cell infiltration, especially that of macrophages, and the levels of cytokines such as IL-6, TNF-α, IL-17 A and MCP-1, were also decreased obviously in S100A4 −/− mice, a finding that is consistent with previous studies that S100A4 recruits macrophages. 44 Furthermore, the NF-κB levels in AOM/DSS-induced colon tissues in S100A4 −/− mice were clearly down-regulated compared with those in WT mice. In vitro, S100A4 could activate the NF-κB signal pathway in macrophages, contributing to the development of CRC by enhancing the proliferation of pre-malignant IECs.…”
Section: Resultsmentioning
confidence: 93%
“…It was recently shown that FSP1 is crucial for proper myosin-IIA assembly and colony-stimulating factor-1 receptor signaling in macrophages and that FSP1 mediates macrophage recruitment and chemotaxis in vivo (34). These data suggest that FSP1 apart from being a marker also has a biological function in macrophages.…”
Section: Discussionmentioning
confidence: 92%